ANALISIS PENERIMAAN PAJAK RESTORAN DAN PAJAK HOTEL SEBAGAI SUMBER PENDAPATAN ASLI DAERAH (STUDI PADA DINAS PENDAPATAN PENGELOLAAN KEKAYAAN ASLI DAERAH KOTA MEDAN) - Vebry Lumban Gaol (Visi Sosial Humaniora, 2020)
Regional Indigenous Revenue is a source of regional income consisting of local taxes, regional retribution and a separate area of wealth management. With the aim of research is analyzing and explaining the contribution, effectiveness and growth rate. The average restaurant tax contribution rate against the regional original revenue is 6.69% and the hotel's tax contribution rate is 4.82%. The restaurant tax growth rate calculation was 5.29% in 2016 and 0.99% in 2017, for hotel tax of 4.54% in 2015 and 3.26% in 2016.